2003
DOI: 10.1080/15287390306375
|View full text |Cite
|
Sign up to set email alerts
|

Biosensor Detection of Neuropathy Target Esterase in Whole Blood as a Biomarker of Exposure to Neuropathic Organophosphorus Compounds

Abstract: Public Reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. 44379.1-LSNeuropathy target esterase (NTE) is the target for neuropathic organophosphorus compounds (OPs) that produce delayed neurotoxicity (OPIDN). Inhibition/aging of brain NTE predicts the potential for OPIDN in animal mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 20 publications
3
26
0
4
Order By: Relevance
“…Brain NTE activity was determined in 9S supernatants by the colorimetric method of Johnson ( Johnson, 1977) with slight modifications (Kayyali et al, 1991;Makhaeva et al, 2003). All reactions were carried out at 37°C for the entire assay.…”
Section: Neuropathy Target Esterase Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…Brain NTE activity was determined in 9S supernatants by the colorimetric method of Johnson ( Johnson, 1977) with slight modifications (Kayyali et al, 1991;Makhaeva et al, 2003). All reactions were carried out at 37°C for the entire assay.…”
Section: Neuropathy Target Esterase Assaymentioning
confidence: 99%
“…Blood NTE activity was determined in 1/100 (v/v) blood hemolysates according to the differential inhibition method of Johnson (Johnson, 1977) with an electrochemical endpoint as described previously (Sigolaeva et al, 2001(Sigolaeva et al, , 2013bMakhaeva et al, 2003). Briefly, 1/100 (v/v) blood hemolysate samples (300 μl) were preincubated for 20 min at 37°C in 50 mM Tris-HCl/0.2 mM EDTA (pH 8.0 at 37°C) with 50 μM PO (sample B) or 50 μM PO plus 250 μM MIP (sample C) (final inhibitor concentrations in a final volume of 400 μl).…”
Section: Neuropathy Target Esterase Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Neuropathy Target Esterase (NTE), is a membrane-bound protein found in neurons of vertebrates (Glynn, 1999;Atkins & Glynn, 2000;van Tienhoven et al, 2002;Li et al, 2003;Makhaeva et al, 2003;Kropp et al, 2004), has been shown to be necessary for embryonic development in mice, and is believed to be involved in cell-signaling pathways and lipid trafficking (Glynn, 1999). NTE has serine esterase activity and can hydrolyze ester, peptide, and amide bonds.…”
Section: Introductionmentioning
confidence: 99%
“…In the second step, the concentration of phenol in the solution is determined either colorimetrically, in the presence of 4-amino antipyrine (Kayyali et al, 1991), or electrochemically, in the presence of tyrosinase enzyme (Sigolaeva et al, 2001;Sokolovskaya et al, 2005). Tyrosinase converts phenol first to catechol and then to o-quinone, which can be measured electrochemically at an electrode (Makhaeva et al, 2003). The current generated by the electrode increases with the amount of o-quinone present, thus giving an indirect measurement of the amount of NTE esterase activity present during the first step.…”
Section: Introductionmentioning
confidence: 99%